Akta przewodów doktorskich i habilitacyjnych Wydziału Kościelnych Nauk Historycznych i Społecznych ATK - Milewski, Dariusz (Archiwa, Biblioteki i Muzea Kościelne, 2011)
Records of doctoral proceedings of the Faculty of Historical and Social Studies contained in the archive of Cardinal Stefan Wyszyński University include not only the opened and completed doctoral proceedings of the faculty but also the records of recognition of doctoral degrees granted by foreign academic institutions. There are in total 89 archived units. There are supplemented by doctoral proceedings, which were opened but not completed for a variety of reasons - 6 units. Together they span the years 1973 to 1999. The complete documentation can be seen in Table 1. The records hare been filed according to their signatures following the rearrangement and cataloguing of the archive. They are therefore filed chronologically. The Table shows the main elements of the doctoral proceedings: - the signed records, - doctorant’s name, - thesis title, - number of pages in each volume of the thesis, - the discipline in which the doctorate was awarded, - the supervisor’s name, - the names of the reviewers, - commencement of the proceedings, - the date of the examination, - the date of the Faculty Board’s decision to award the degree, - the date and number of the doctoral certificate. The information in this article is primarily intended for those researching the history and studies carried out in the faculty.